Planning aspects for water culture development in Gaza strip - El Sheikh R.A.; Hamdan S.M.; Abo Shammala A.S. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
The Palestinian Water Authority (PWA) in its policy has paid attention to the public awareness but has never applied the related programs in a sustainable way. Other NGOs try to cover small awareness programs in their projects in coordination with PWA in small scattered efforts which have not resulted in a sensitive respond of the public. Conceptual planning taking in consideration the current socioeconomic reasons behind the weak respond of consumers has been targeted. The real costs of water paid by the consumers to secure desalinated water are the driving force for this plan. Enforcement of regulations, awareness and incentives for consumers who are committed by water conservation are strong means for a sustainable water resources management.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)